Wariantywność form fleksyjnych rzeczowników w listach polskich z lat 1525-1550 (rzeczowniki rodzaju nijakiego; rzeczowniki typu podskarbi, podczaszy; pluralia tantum; pluralne nazwy geograficzne; formy liczby podwójnej) - Osiewicz, Marek (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2009)
The article is the third and last part of the description of inflectional variation of nouns in the letters in Polish from the first half of the 16th century. The present chapter concerns the neutral gender nouns, the nouns of the type podskarbi (treasurer), podczaszy (cup-bearer), the nouns belonging to the category plurale tantum, plural geographical terms, as well as the nominal forms of dual number. The analysis embraced only these grammatical categories which revealed, in excerpted letters, the oppositions of isomorphic character significant for the process of normalization of the Polish language. With regard to the neutral gender nouns these are: instrumental and locative cases of the singular number as well as genitive, dative, instrumental and locative cases of the plural number. Separate attention was paid to the inflection of the noun książę (prince). Within the nouns of the type podskarbi and podczaszy, the author discussed the forms of the instrumental case of the singular number and of the nominative, dative, accusative and instrumental cases of the plural number. With reference to plural nouns, the analysis concerned the forms of the dative and accusative cases of the noun ludzie (people) and the dative and locative cases of the plural geographical names. The rivalry between the dual and plural forms was subject to a complex analysis. The condition of inflectional variation of the above specified nouns, confirmed in the letters in Polish, shows considerable similarity to the condition depicted in other texts originating from the same period. The violations of the 16th-century norms result from the operation of purely innovative tendencies and, mostly, refer to the more frequent usage of the endings -em in the instrumental case in the singular number, -am in the dative case in the plural number and -ach in the locative case in the plural number of neuters as well as to a higher percentage of the occurrence of a new form of the accusative case of the plural number of the nouns such as poddany (serf) and the plural forms of the genitive and locative cases of the nouns preceded by the numerals dwa (two) and oba (both). The last chapter of the article sums up the completed analysis. It indicates that, as far as the inflection of nouns is concerned, the Polish language used in the letters shows a relatively small degree of normalization. Among the variants certified in the analysed correspondence, the progressive forms prevail, which proves the innovative character of the variety of the language represented in the letters. The range of inflectional variation is wider than in printed texts from that period, however, the differences are not so considerable. The violations of the inflectional norms in printed texts, confirmed in the letters, result from an approximately uniform influence of the tendencies promoting progressive forms as well as the conservative tendencies. Moreover, the analysis showed that the Polish language used in the letters is closer to the language of the texts of Glaber than to the Polish language of paleotypes, characterised by much more restrictive approach to the traditional norm.